SEQUENCE DIVERSITY AND MOLECULAR EVOLUTION ANALYSIS OF INTERNATIONAL TOMATO BASED ON THE ENTIRE ITS REGION - Al-Shahwany, Ayyad W.; Hawash, Mohammed M.; A. Hajeej, Thaer Hamid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aimed to assess the genetic diversity and molecular evolution of tomato (Solanum lycopersicum) populations from various countries, which hold significant potential for future breeding strategies and germplasm conservation. To achieve this, a total of 15 sequences deposited in GenBank were analyzed using the complete internal transcribed spacer (ITS) region of the nuclear ribosomal DNA (nrDNA). The spacer sequence lengths ranged from 156 base pairs (bp) in the Swedish tomato to 713 bp in the Palestinian tomato. A notable variation in GC content was observed, with the Thai tomato exhibiting the highest value (67.48%) and the South Korean tomato the lowest (49.56%). Phylogenetic trees were constructed using both the distance-based Neighbor-Joining (NJ) and Maximum Parsimony (MP) methods. Sequence analysis revealed 38 monomorphic (invariable) sites and 15 polymorphic sites, of which 14 were singleton variable sites and one was parsimony-informative. Alignment of the 15 sequences enabled the identification of five haplotypes. The estimated transition/transversion bias (R) was 17.339, indicating a greater frequency of transitions over transversions in this region. Neutrality tests, including Tajima’s D and Fu and Li’s statistics, produced statistically significant results. The highest levels of genetic diversity were observed in South Korean, Iraqi, and Indian tomato samples.